Intraoperative dermoscopy features of subungual squamous cell carcinoma: a study of 53 cases. (1st January 2021) - Carlioz, V.; Perier‐Muzet, M.; Debarbieux, S.; Amini‐Adle, M.; Dalle, S.; Duru, G.; Thomas, L.
Abstract: Background: Subungual squamous cell carcinoma (SU‐SCC) is the most common malignant tumour of the nail unit. Intraoperative nail dermoscopy has been described only for pigmented tumours, onychomatricoma and glomus tumours. Aim: To establish a description of intraoperative dermoscopic features of SU‐SCC. Methods: A single‐centre retrospective cohort of 53 SU‐SCC cases over a 5‐year period was reviewed by six examiners who individually scored 31 intraoperative dermoscopic features as present or absent. For each feature, the frequency and interobserver agreement was evaluated, then the data were compared and a consensus was reached. Results: No feature had perfect or substantial interobserver agreement. Regarding anatomy and architecture, most tumours involved both the nail bed and nail matrix ( n = 34, 64.2%) and had nonparallel lateral side edges ( n = 36, 67.9%). Regarding vascular features, several different patterns were found: dotted vessels ( n = 49, 92.5%), irregular vessels ( n = 47, 88.7%), curved vessels ( n = 46, 86.8%), sagittal vessels ( n = 45, 84.9%), milky‐red areas ( n = 42, 79.2%), linear and regular vessels ( n = 30, 56.6%), coiled and hairpin vessels ( n = 23, 43.4%), and arborizing vessels ( n = 16, 30.2%). Pigmented dermoscopy structures included dotted purpura, grey granulation and splinter haemorrhages, which were found in 49 (20.8%), 9 (17%) and 9 (17%) cases, respectively. Other dermoscopic signs were pink background, translucent structureless area, whitish scaly areas, distal plug, yellowish scales and dots, and 'digitiform' proximal edge, which were found in 49 (84.9%), 49 (84.9%), 43 (81.1%), 37 (69.8%), 28 (52.8%) and 22 (41.5%) cases, respectively. Conclusion: Analysis of this first large series of SU‐SCC studied by intraoperative dermoscopy suggests that it gives useful information to better approach the diagnosis and to target biopsies.